Equação do 1º grau: métodos de resolução e análise de erros no ensino médio - Freitas, Marcos Agostinho de (2002)
This research studies the aspects related to theprocedures of the first-degree equations solution used by first-year students of a private secondary school of São Paulo. In a more specific way, it refers to the errors related to the conceptual aspects and to the solution methods of these equations. The research consisted on the application of na investigative instrument that contains 24 first-degree equations, with whole coefficients, and interviews with these students. The analysis of correct and incorrect solution procedures revealed a strong influence of the associated techniques mechanization to the use of sentences such as: isolate the x , pas and change the signal . In analyzing the students mistakes, this study aims to point out ways for new approaches on the primary and secondary school solution methods of equations